COST AND PROFIT ANALYSIS OF BALI GOLDISH FARMING AT POKDAKAN KOIYOGAN KAZOKU RANA - Ni Luh Desi Puspitayanti; Ni Putu Anglila Amaral; I Made Budiasa (Fakultas Pertanian dan Bisnis Universitas Mahasaraswati Denpasar, 2026)
The waters in Indonesia are very vast and consist of freshwater and seawater. Indonesia has a high diversity of freshwater resources, one of which is goldfish. This study aims to analyze the costs and benefits of Bali goldfish farming at the Koiyogan Kazoku Rana fish farming group and the feasibility of Bali goldfish farming at the Koiyogan Kazoku Rana fish farming group. This research was conducted from July to August 2024 at the Koiyogan Kazoku Rana fish farming group located in Bunutin Village, Bangli District, Bangli Regency, Bali Province. This study uses a quantitative method using cost and income data analysis, business feasibility. The results of this study indicate that the production cost of Bali goldfish at the Koiyogan Kazoku Rana fish farming group is IDR 3,919,042 per harvest, consisting of fixed costs of IDR 1,658,542 per harvest and variable costs of IDR 2,260,500 per harvest. The income generated is 11,280,958 with a revenue value of Rp 15,200,000 and a production cost value of Rp 3,919,042 per harvest. The R/C value is greater than 1, which is 3.8. An R/C value greater than one indicates that the Bali goldfish farming business at the Koiyogan Kazoku Rana Layal Pokdakan is suitable for development.